Parallel simulation techniques for large-scale networks. - Bhatt, S. (IEEE Communications magazine)
Simulation has always been an indispensable tool in the design and analysis of telecommunication networks. Due to performance limitations of the majority of simulators, usually network simulations have been done for rather small network models and for short timescales. In contrast, many difficult design problems facing today's network engineers concern the behavior of very large hierarchical multihop networks carrying millions of multiprotocol flows over long timescales. Examples include scalability and stability of routing protocols, packet losses in core routers, of long-lasting transient behavior due to observed self-similarity of traffic patterns. Simulation of such systems would greatly benefit from application of parallel computing technologies, especially now that multiprocessor workstations and servers have become commonly available. However, parallel simulation has not yet been widely embraced by the telecommunications community due to a number of difficulties. Based on our accumulated experience in parallel network simulation projects, we believe that parallel simulation technology has matured to the point that it is ready to be used in industrial practice of network simulation. This article highlights work in parallel simulations of networks and their promise